Retos y Desafíos de los Enfermeros en la Actualidad: Un Enfoque para Mejorar el Desempeño Profesional en un Hospital Público en Ecuador - Cuenca Cuenca, Yajaira Marisol (My University, 2025)
Currently, nursing professionals play an indispensable role within the global healthcare system; however, they face challenges that negatively influence their job performance, such as: long working hours, continuous exposure to stress, work overload, critical decision-making, high patient demand, and staff shortages. Therefore, it is important that healthcare management design strategies that promote job satisfaction, such as staff motivation and ongoing training, from an organizational culture perspective. The objective of this research is to determine the main challenges and challenges currently faced by the nursing professional during professional practice, a study was carried out in a Basic Hospital, with a total of 30 participants who work in said entity, a data collection instrument was applied and the responses were tabulated in the IBM SPSS 25.0 statistical program within the results obtained 73.3% indicate work overload compared to 63% that indicates lack of personnel, these two aspects being the most influential in the development of work stress, on the other hand, 66% identical that the coordination between nursing leaders is deficient and only 50% stated that they receive continuous training within the job, all these aspects are documented in the literature, due to the health crisis that Ecuador is facing, it is necessary to replicate this type of studies in other institutions in order to contextualize the challenges and challenges of the current health system and design improvement strategies in order to optimize available resources and achieve the long-awaited excellence of care without sacrificing the physical, psychological and mental health of the nursing staff. Keywords: Nursing Professionals, Quality of Care, Job Performance, Healthcare Management .
Actualmente los profesionales de enfermería cumplen un rol indispensable dentro del sistema sanitario a nivel global, no obstante, enfrenta retos y desafíos que influyen negativamente en su desempeño laboral como: largas jornadas laborales, exposición continua al estrés, sobrecarga laboral, toma de decisiones críticas, la alta demanda de pacientes y escasez de personal, por ello es importante que desde la gestión sanitaria se diseñen estrategias que favorezcan la satisfacción laboral, como la motivación del personal, capacitación continua, desde un enfoque de cultura organizacional. El objetivo de la presente investigación es determinar los principales retos y desafíos que enfrenta actualmente el profesional de enfermería durante la práctica profesional, se realizó un estudio en un Hospital Básico, con un total de 30 participantes que laboran en dicha entidad, se aplicó un instrumento de recolección de datos y se tabulo las respuestas en el programa estadístico IBM SPSS 25.0 dentro de los resultados obtenidos el 73,3% señala la sobrecarga laboral frente a un 63% que indica falta de personal, siendo estos dos aspectos los más influyentes en desarrollo de estrés laboral, por otro lado el 66% idéntico que la coordinación entre los lideres de enfermería es deficiente y solo el 50% afirmo recibir capacitación continua dentro el trabajo, todos estos aspectos están documentados en la literatura, debido a la crisis sanitaria que enfrenta el Ecuador es necesario replicar este tipo de estudios en otras instituciones a fin de contextualizar los retos y desafíos propios del sistema sanitario actual y diseñar estrategias de mejora con el fin de optimizar los recursos disponibles y lograr la tan anhelada excelencia de cuidado sin sacrificar la salud física, psicológica y mental del personal de enfermería
Keywords: PROFESIONALES DE ENFERMERÍA; CALIDAD DE ATENCIÓN; DESEMPEÑO LABORAL; GESTIÓN SANITARIA